Medyczny poradnik jezykowy angielsko-polski - Klos, Jan.; Olech, Ewa. (Lublin : Norbertinum, 1993)
A pocket dictionary of medical terms from English to Polish.
Title on added t.p.: English-Polish medical pocket dictionary.
Keywords: Medicine -- Dictionaries; English language -- Dictionaries -- Polish